Temperatures and treeline elevation in the Sierra Nevada de Mérida of the Venezuelan Andes - Vicente Marcano; Rafael Navarro-González; Christopher P. McKay (Arctic, Antarctic, and Alpine Research)
We report here on two extensive data sets across the tree line in the Sierra Nevada de Mérida in the Venezuelan Andes. First, we describe the tree distribution with elevation at this site. Second, we report on several years of temperature data beginning in 2001 for the soil surface, 10, 20, and 40 cm depth from 2,000 to 4,978 m elevation. The tree line at this site is dominated by Polylepis and is located near 4,100 m. At the tree line, the annual mean temperature at 10 cm depth was 6.66°C with an annual maximum temperature of 13°C and an annual minimum temperature of 1.4°C; the lowest maximum temperature for any day of the year was 6°C, so though there is not continuous growth, every day of the year the temperature gets high enough that some growth is possible. The mean annual air temperature was 6.4°C. The topographic lapse rate across the tree line is 5.7°C/km for all depths. Below 3,500 to 2,500 m elevation in the cloud forest zone the topographic rate decreases to 0.9°C/km. Our results are consistent with the emerging model of temperature correlation with the elevation of tree line. Temperature archive data set identifier: https://zenodo.org/records/12628498.